Low Interest Rates – A Real Threat to German Banks or First-Class Whining?! - Jessica Hastenteufel; Lena Fuchs (Managerial Economics)
The current phase of low interest rates poses major challenges for banks. A continuous decline in the interest result, which is so important for the profitability of banks, has been observed for years, as it is becoming increasingly difficult for banks to generate sufficient income from the interest margin. This is partly due to the European Central Bank’s expansive monetary policy. However, other factors, such as advancing digitization, also play a role here. The structure of the German banking market and the mostly strong focus of German banks on interest-bearing business are also increasingly becoming a problem. Still, the question arises, whether the current phase of low interest rates is actually a serious threat to banks or whether they are complaining at a high level.